The role of ai tools in improving listening and speaking skills in university foreign language courses - Lemeshchenko-Lagoda, Viktoriia; Лемещенко-Лагода, Вікторія Володимирівна (My University, 2025)
EN: The article is devoted to the possibilities of implementing artificial intelligence technologies into the foreign language learning process for students of higher education institutions. In particular, it considers AI tools (NaturalReader, Gliglish, Lingolette, Luvvoice) that can improve students' speaking and listening skills and increase their motivation for personal self improvement. /// UA: Статтю присвячено розгляду можливостей імплементації технологій штучного інтелекту у процес вивчення іноземної мови студентами закладів вищої освіти. Зокрема, розглядаються АІ-інструменти (NaturalReader, Gliglish, Lingolette, Luvvoice), які здатні покращити навички говоріння та аудіювання студентів та підвищити їх мотивацію до персонального самовдосконалення.
Роль інструментів штучного інтелекту в покращенні навичок аудіювання та говоріння під час вивчення курсу іноземної мови у закладах вищої освіти
Keywords: artificial intelligence; AI tools; foreign language; listening skills; speaking skills; штучний інтелект; інструменти штучного інтелекту; іноземна мова; навички аудіювання; навички говоріння